Production and Carbon Emission Calculation of Bricks Incorporating Construction And Demolition Waste and Pet Pellets - K.C, Anusha; Maharjan, Prakriti; Shrestha, Sujan Kumar; Rayamajhi, Sujan; Shrestha, Anil Ratna (Journal of Advanced College of Engineering and Management, 2023)
The study aims to incorporate solid wastes in the brick where cement is the binding agent and perform the comparative analysis of mechanical properties (compressive strength, density, and water absorption). Polyethylene Terephthalate (PET), and Construction and Demolition waste are the wastes that partially replace sand in the mixture of cement and sand. The compressive strength, water absorption, and dry density of the waste-incorporated bricks are determined which are compared with all parameters of the traditional bricks. The brick with 2% PET showed the best compressive strength of 13.515 MPa. While determining the carbon emissions of composite bricks it showed 0.6 to 0.9 kg CO2 had been generated from the raw material extraction and processing phase, however, the production phase involved no carbon emission because the process was manual and involved no heating or firing. The composite bricks have the potential to be used as structural elements, however, the composite bricks require further study for the optimization of binder content with respect to cost, compressive strength, and carbon emission.